1995
DOI: 10.1136/vr.137.14.337
|View full text |Cite
|
Sign up to set email alerts
|

Mice as carriers of Salmonella enteritidis on persistently infected poultry units

Abstract: Evidence of the possible role of wild mice in the epidemiology of Salmonella enteritidis infection on broiler breeder and layer breeder units was obtained by a bacteriological examination of local mice. Persistent S enteritidis infection in birds on these units had been a problem and a high proportion of the mice were found to carry salmonella. S enteritidis was isolated from the liver and the intestine of most of the mice, indicating a systemic infection. Three-week-old chicks were infected by contact with dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 0 publications
4
96
1
Order By: Relevance
“…There is evidence that S. Enteritidis spreads rapidly from infected day old chicks to pen mates reared on litter 78,81 . Poultry may also get infected from feed 43,66 , water 36 , rodents 4,17,40 , or by contact with other poults or chicks. Infection by these routes in chicks reached 100% within seven days of contact 81 .…”
Section: Horizontal Infection Of S Enteritidis In Poultrymentioning
confidence: 99%
“…There is evidence that S. Enteritidis spreads rapidly from infected day old chicks to pen mates reared on litter 78,81 . Poultry may also get infected from feed 43,66 , water 36 , rodents 4,17,40 , or by contact with other poults or chicks. Infection by these routes in chicks reached 100% within seven days of contact 81 .…”
Section: Horizontal Infection Of S Enteritidis In Poultrymentioning
confidence: 99%
“…Most of the cases were associated with consumption of contaminated eggs laid by infected chickens (6,33,38). Chickens are probably infected on poultry farms by field mice, which serve as a reservoir for S. enterica serovar Enteritidis (10,23,25). Therefore, infection of mice is believed to be a link in the natural transmission cycle of S. enterica serovar Enteritidis.…”
mentioning
confidence: 99%
“…Mode of SE infection in chickens and chicken flocks) was referred to and investigated as a model in the SE vaccine development. However, a recent study and our survey results suggested that SE contamination/infection of chickens disseminates through mouse-mediated transmission between hen houses (Davies RH et al 1995, Henzler DJ et al 1992, and not by vertical infection as in PD infection model (Yamane Y et al 2000). Unlike SE infection of mice and humans (Guiney DG Bohez L et al 2007, and the infection is not systemic and manifests no symptoms in infected chickens.…”
Section: Incidence/percentagementioning
confidence: 78%